2014
DOI: 10.1073/pnas.1417820111
|View full text |Cite
|
Sign up to set email alerts
|

Label-free imaging of Schwann cell myelination by third harmonic generation microscopy

Abstract: Understanding the dynamic axon-glial cell interaction underlying myelination is hampered by the lack of suitable imaging techniques. Here we demonstrate third harmonic generation microscopy (THGM) for label-free imaging of myelinating Schwann cells in live culture and ex vivo and in vivo tissue. A 3D structure was acquired for a variety of compact and noncompact myelin domains, including juxtaparanodes, Schmidt-Lanterman incisures, and Cajal bands. Other subcellular features of Schwann cells that escape tradit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 34 publications
3
49
0
Order By: Relevance
“…Using CARS imaging, the myelin sheath is directly labelled thank to its rich content in lipids and it appears as a large band surrounding axons. These results are consistent with previous analysis by specialists in optics [18,19] and in peripheral nerve biology [7,14].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Using CARS imaging, the myelin sheath is directly labelled thank to its rich content in lipids and it appears as a large band surrounding axons. These results are consistent with previous analysis by specialists in optics [18,19] and in peripheral nerve biology [7,14].…”
Section: Discussionsupporting
confidence: 93%
“…Using YFP axonal labelling, we found that this hatched signal came from a domain outlining the axon (red arrowheads, Figure 1I) and a domain outlining the myelin sheath (black arrowheads, Figure 1I). Taken together these data and previous reports in the literature [14] indicated that THG signal was produced at interfaces of the myelin with the axon (red arrowheads, Figure 1H,I) and of the myelin and the extracellular environment (black arrowheads, Figure 1H,I). These THG signals appeared as very large bands when the focus reached the surface of these interfaces (red and black lines, Figure 1H).…”
Section: Second Third Harmonics and Cars Imaging In The Sciatic Nesupporting
confidence: 89%
“…Cortical areas with one sign (V1, AL, AM) may all represent similar thalamocortical (or intracortical) fiber orientations compared to areas with the opposite sign (RL, LM, PM). These fiber orientations would then be reflected in the orientations of myelin and even blood vessels 22,46,47 as measured with THG imaging that contribute to EALs.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to OCM's dependence on differential tissue scattering, THG microscopy is a nonlinear imaging approach that generates a signal at lipid–water interfaces due to nonlinear coherent scattering (Weigelin, Bakker, & Friedl, ). Again based on the unique biophysical properties of myelin, THG can be used for label‐free imaging of myelin in vivo (Farrar et al, ; Lim et al, ). THG imaging requires high intensity long wavelength lasers and high laser power in order to generate bright signals thus photodamage or thermal injury is a possibility.…”
Section: Optical Approaches For Live Myelin Imagingmentioning
confidence: 99%